2016
DOI: 10.2527/jas.2015-9478
|View full text |Cite
|
Sign up to set email alerts
|

Bixin uptake and antioxidative effect and role in immunoregulation in domestic cats1

Abstract: Bixin, a carotenoid found in the seed of the Annatto plant, , is a potent antioxidant. Carotenoids are readily absorbed from the diet; therefore, the purpose of this study was to examine uptake of bixin by plasma, lipoproteins, and leukocytes after dietary supplementation in domestic cats and to assess effects on immune response. Female domestic short hair cats (3 yr old; 4.79 ± 0.13 kg BW) were fed a single dose of 0, 1, 5, or 10 mg bixin, and blood was taken at 0, 1, 2, 4 and 8 h after administration ( = 6/t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…They reported that the increase in stress resistance led to a decrease in lipids, DNA, and protein oxidation. To our knowledge, no similar studies are available for AE, bixin, or dT3, although in vitro and in vivo antioxidant activity, as well as anti-inflammatory effects, have been reported [18,[29][30][31]. Although bixin did not improve resistance against oxidative or thermal stress or extend longevity at the concentrations tested in this study, different bixin concentrations might produce a beneficial outcome.…”
Section: Discussionmentioning
confidence: 55%
“…They reported that the increase in stress resistance led to a decrease in lipids, DNA, and protein oxidation. To our knowledge, no similar studies are available for AE, bixin, or dT3, although in vitro and in vivo antioxidant activity, as well as anti-inflammatory effects, have been reported [18,[29][30][31]. Although bixin did not improve resistance against oxidative or thermal stress or extend longevity at the concentrations tested in this study, different bixin concentrations might produce a beneficial outcome.…”
Section: Discussionmentioning
confidence: 55%
“…On a short-term basis, the gestating sow is able to mobilize her body reserves of protein, energy, and minerals to prioritize pregnancy over growth, but the further effects of under- or oversupplying nutrients are not always easy to discern ( Huber, 2019 ). Concerning primiparous sows, precision feeding is specifically interesting as, although they have a greater body protein and weight gain during gestation, they are able to satisfy their requirements for maternal and fetal growth without digging into their own reserves ( Buis, 2016 ). In that study, group-housed gilts fed with a PF strategy during gestation had a similar LS and litter growth than gilts fed with a CF strategy, but PF gilts ate more (+9%) and tended to loose less weight during the subsequent 21 d lactation period, which may benefit long-term reproductive performance.…”
Section: Discussionmentioning
confidence: 99%
“…New technologies have been developed to feed the group-housed sows, e.g., with automatic feeding stations that are sometimes designed to deliver several feeds. More generally, the development of precision feeding ( PF ) gives new opportunities to better take into account, in real time, the factors influencing nutritional needs ( Brossard et al, 2016 ; Buis et al, 2016 ). In this context, models and decision support systems ( DSS ) have been developed to be integrated into automatic feeders for growing pigs ( Hauschild et al, 2012 ; Cloutier et al, 2015 ; Brossard et al, 2017 ) and more recently for sows ( Gaillard et al, 2019 ; Gauthier et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…When challenge by subsequent allergens, IgE-coated mast cells and recruited eosinophils release active mediators to promote smooth muscle contraction, vascular permeability and mucus production, resulting in reversible lower airway obstruction in asthmatic individuals termed as acute asthma attack [39]. Studies have demonstrated Bixin shows an immunomodulatory role of in domestic animals [40,41]. In this study, we found that treatment with Bixin signi cantly reduced both the levels of Th2 cytokines and the in ammatory cells in ltration in airway of an acute asthma murine model (Fig.…”
Section: Discussionmentioning
confidence: 99%